Determinants of the variability in respiratory exchange ratio at rest and during exercise in trained athletes - Goedecke, J. H.; Gibson, A. S.; Grobler, L.; Collins, M.; Noakes, T. D.; Limbert, E. V. (American Journal of Physiology, Endocrinology and Metabolism, 2000)
We examined the variability and determinants of the respiratory exchange ratio (RER) at rest and during exercise in 61 trained cyclists. Fasting (10-12 h) RER was measured at rest and during exercise at 25, 50, and 70% of peak power output (W(peak)), during which blood samples were drawn for [lactate] and [free fatty acid] ([FFA]). Before these measurements, training volume, dietary intake and muscle fiber composition, [substrate], and enzyme activities were determined. There was large interindividual variability in resting RER (0.718-0.927) that persisted during exercise of increasing intensity. The major determinants of resting RER included muscle glycogen content, training volume, proportion of type 1 fibers, [FFA] and [lactate], and %dietary fat intake (adjusted r(2) = 0.59, P < 0.001). Except for muscle fiber composition, these variables also predicted RER at 25, 50, and 70% W(peak) to different extents. The key determinant at 25% W(peak) was blood-borne [substrate], at 50% was muscle [substrate] and glycolytic enzyme activities, and at 70% was [lactate]. Resting RER was also a significant determinant of RER at 25 (r = 0.60) and 50% (r = 0.44) W(peak).